Deploying an Application to Cloud Platform Using Continous Integration and Continous Delivery - Albaihaqi, Muhammad Fauzan; Wilda, Anisa Nurul; Sugiantoro, Bambang (Proceeding International Conference on Science and Engineering, 2020)
Cloud Computing is the best way for bussiness owner deploy an application to reduce cost issue because it is implement pay as you go concept. Generally, an application on production level or deployed into cloud instance should not have any error or bug. It should be tested and maintain properly. The problem when an application have intensive development that takes more effort to test the application and deploy. So, need a strategy to deploy an application into cloud instance to make the proccess more efficient. Nowadays, Version Control System (VCS) platform provide Continous Integration and Continous Delivery (CI/CD) feature. Users can utilize that platform to perform automated test and deployment easily. This reasearch purposed to examine how to use CI/CD feature and evaluate it in case of deploying web application to Cloud Platform. Researcher use Gitlab wich is provide CI/CD feature for free and deploy the app to Amazon Web Service. The researcher also utilize docker container to accommodate all processes. The result are Continous Integration can improove application quality because most lines of codes are tested using unit or feature test scenario. Using CI/CD feature improove security issue of deployment. Deployment proccess run automatically without human intervention so it will reduce human error factors. This feature also ensure high availability of an application. Deployment proccess will take zero downtime. The application can quickly update without any downtime and configuration. Last, docker container take an important role for deployment of application into cloud instance.